ANALISIS ALTERNATIF PENEMPATAN SATELIT LAPAN A2 DI ORBIT - Nizam Ahmad (Lembaga Penerbangan dan Antariksa Nasional, 2010)
The preliminary orbit design of LAPAN A2 satellite takes an assumption that the satellite will be launched on October, 2011. This design used a scenario of satellite placement in orbit at altitude of about 650km, 800 km and 870 km and inclinations of 8, 10 and 20. The orbit analysis shows that if the satellite will be launched in Sriharikota, India, it will be only possible for inclination of 20. A satellite at an altitude of 800 km is more effective for a remote sensing mission than that of 650 km and 870 km, because it will pass Indonesia region 14 times a day with the total swath width is 4205.75 km and time in view is about 11 minutes. In addition, the satellite will revolve the earth 14 times a day with the periode of about 100.85 minutes. Keywords: Satellite, Orbit